'Smoking genes': a genetic association study. - Zoraida Verde; Catalina Santiago; José Miguel Rodríguez González-Moro; Pilar de Lucas Ramos; Soledad López Martín; Fernando Bandrés; Alejandro Lucia; Félix Gómez-Gallego (PLoS ONE, 2011)
Some controversy exists on the specific genetic variants that are associated with nicotine dependence and smoking-related phenotypes. The purpose of this study was to analyse the association of smoking status and smoking-related phenotypes (included nicotine dependence) with 17 candidate genetic variants: CYP2A6*1×2, CYP2A6*2 (1799T>A) [rs1801272], CYP2A6*9 (-48T>G) [rs28399433], CYP2A6*12, CYP2A13*2 (3375C>T) [rs8192789], CYP2A13*3 (7520C>G), CYP2A13*4 (579G>A), CYP2A13*7 (578C>T) [rs72552266], CYP2B6*4 (785A>G), CYP2B6*9 (516G>T), CHRNA3 546C>T [rs578776], CHRNA5 1192G>A [rs16969968], CNR1 3764C>G [rs6928499], DRD2-ANKK1 2137G>A (Taq1A) [rs1800497], 5HTT LPR, HTR2A -1438A>G [rs6311] and OPRM1 118A>G [rs1799971]. We studied the genotypes of the aforementioned polymorphisms in a cohort of Spanish smokers (cases, N = 126) and ethnically matched never smokers (controls, N = 80). The results showed significant between-group differences for CYP2A6*2 and CYP2A6*12 (both P<0.001). Compared with carriers of variant alleles, the odds ratio (OR) for being a non-smoker in individuals with the wild-type genotype of CYP2A6*12 and DRD2-ANKK1 2137G>A (Taq1A) polymorphisms was 3.60 (95%CI: 1.75, 7.44) and 2.63 (95%CI: 1.41, 4.89) respectively. Compared with the wild-type genotype, the OR for being a non-smoker in carriers of the minor CYP2A6*2 allele was 1.80 (95%CI: 1.24, 2.65). We found a significant genotype effect (all P≤0.017) for the following smoking-related phenotypes: (i) cigarettes smoked per day and CYP2A13*3; (ii) pack years smoked and CYP2A6*2, CYP2A6*1×2, CYP2A13*7, CYP2B6*4 and DRD2-ANKK1 2137G>A (Taq1A); (iii) nicotine dependence (assessed with the Fagestrom test) and CYP2A6*9. Overall, our results suggest that genetic variants potentially involved in nicotine metabolization (mainly, CYP2A6 polymorphisms) are those showing the strongest association with smoking-related phenotypes, as opposed to genetic variants influencing the brain effects of nicotine, e.g., through nicotinic acetylcholine (CHRNA5), serotoninergic (HTR2A), opioid (OPRM1) or cannabinoid receptors (CNR1).